Volcanology and geochemistry of selected kimberlites from the Lulo kimberlite field, Angola - Moldenhauer, Jena (Department of Geological Sciences, 2025)
Abstract The area under study is the Lulo Kimberlite Field in the province of Lunda Norte, Angola, which is located 630 km east of the capital, Luanda. This 3000 km2 concession is one of the world's most abundant alluvial diamond fields, producing high value Type IIa diamonds, as well as hosting a significant number of kimberlite pipes. Within Angola, there are hundreds of known kimberlite bodies of which, it is estimated, far fewer than 50% have been studied and fewer than 5% have economic diamond grades (Pereira et al., 2003). With ongoing exploitation of predominantly high-grade alluvial deposits, depletion of the diamond reserves demands continual and improved exploration of primary sources. Alluvial diamond mining within the Lulo Field has yielded large, high value diamonds along the Cacuilo River. These diamonds are anhedral in morphology and show sharp edges with little abrasive signs of travel, indicating that their primary kimberlite source is likely nearby. With more than 560 geophysical anomalies having been identified in the Lulo Field, 164 have been drilled, with 141 shown to be kimberlitic (Lucapa Diamond Company, 2024). This study aims to conduct a reconnaissance survey of volcaniclastic kimberlites within these pipes to classify eruptive styles, providing insights into the internal geology of pipes with implications for diamond grade bulk sampling. A total of 52 kimberlite targets were sampled, yielding 83 thin sectionsfor petrographic analysis and eight representative hypabyssal kimberlites for bulk rock geochemistry, through collaboration with Lucapa diamonds. Each one of the 83 thin sections were described using a petrographic microscope and classified following the scheme of Scott Smith et al. (2018) and Webb & Hetman (2021), with 22 chosen as representative samples. Petrographic analyses of the thin sections allowed for the classification of the kimberlites, at the most primary form of subdivision, as either coherent or magmaclastic (Webb & Hetman, 2021). Within the magmaclastic subsection, pyroclastic kimberlites are classified as Fort à la Corne-type pyroclastic kimberlites (FPK) and abundant resedimented volcaniclastic kimberlites (RVK) are also observed interbedded with the FPKs. The classification of the Lulo kimberlites as FPKs is based on their clast supported texture, olivine-dominated magmaclasts, and ultra-fine serpentine and carbonate cement. The magmaclasts display varied morphologies and include cored and uncored varieties, with a wide range of olivine macrocrysts abundances and low proportion of crustal xenoliths further supporting the classification. Furthermore, the presence of RVKs is confirmed due to the predominant clastic texture, abundant quartz and commonly seen broken grains. The identification of kimberlites as predominantly FPK and RVK indicates an explosive eruptive style that led to pipe excavation and post-eruptive reworking. Comparisons with other kimberlite fields, such as the Voorspoed mine in South Africa and the Lac de Gras kimberlite field in Canada, reveals similarities in internal pipe geology to those in the Lulo field and thus are comparable to kimberlite pipes within Diavik and Ekati mines alike. Thus, the Lulo field kimberlites pipes are classified as Class 3 pipes following the scheme of Skinner and Marsh (2004) or Lac de Gras type following the scheme of Scott Smith (2008). Geochemical analysis shows the Lulo kimberlites share characteristics with South African Group I kimberlites, known for their diamondiferous nature. However, certain deviations, such as depleted MgO and enriched Al₂O₃ and Nb concentrations, suggest crustal contamination that is further supported by a contamination index > 1.0 for all bulk-rock samples. Exploration initiatives, including drilling and bulk sampling, are directed at determining diamond grade and identifying the primary source of the high-value, Type IIa alluvial deposits. Kimberlite pipes within the Lulo field, classified as Class 3 pipes, consist of multiple volcaniclastic units (FPK and RVK) within individual pipes, indicative of considerable variability in diamond content. This heterogeneity underscores the importance of detailed stratigraphic analysis to enhance the accuracy of grade estimation. Olivine macrocrysts, which serve as key indicators of diamond-bearing potential, range from 25 to 53 vol.% in FPKs, reflecting mantle-derived material with varying degrees of sorting (ranging from poorly to well sorted) across different pipes. As a comprehensive assessment across the full length of boreholes has not yet been conducted, olivine macrocryst abundance and sorting remains speculative. A thorough understanding of internal pipe geology and olivine distribution is essential for refining diamond exploration and sampling strategies. Moreover, for the RVKs, the proportion of externally derived material may dilute grades and should therefore be considered. Due to the favourable geological setting of the Lulo Mine and its geological and geochemical similarity to other diamond-rich kimberlite occurrences, it can be inferred that Lulo kimberlites hold significant potential for high-grade diamond deposits. However, current bulk sampling for diamond grades is primarily conducted at the surface for each pipe. Accurate diamond grade estimation requires understanding the internal geological variation within a kimberlite, as surface sampling alone may not represent the true diamond potential of deeper units. Therefore, understanding the internal geology of each pipe is essential, as it significantly influences diamond grades during bulk sampling campaigns aimed at discovering high-value stones. This study highlights the importance of integrating detailed petrographic, geochemical, and geological analyses to fully understand the factors controlling diamond grade, providing valuable insight for the future exploration of Angola's primary diamond sources.